Keeping poultry in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East African regional program has selected six sites to test interventions that address risks related to climate change and variability. Featured here is the Lower Nyando site in Kenya, where ongoing activities are showing how keeping poultry is a way to diversify livelihoods and income, which in the long term could help create resilience to climate change. Photo: K. Trautmann